FORMATION OF THE DIGITAL EDUCATIONAL ENVIRONMENT MODEL OF A PEDAGOGICAL UNIVERSITY - Bidaibekov, Е.Ы.; Grinshkun, В.В.; Kurmangaliyeva, Н.А. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2022)
The modern information society makes new demands on higher education. And this, in turn, leads to global changes in the conditions for the functioning of universities and the formation and development of a digital educational environment (DEE) of universities based on the revision and development of many traditional approaches to organizing their work and applied educational technologies. The aim of the work was to determine the structural components of the formation of DEE, based on the integration of technologies "Industry 4.0". The structural-content model of DEE consists of functional-target, theoretical-methodological, content-procedural, analytical-resultative blocks, which show the relationship of the main components in the organization of the educational process. In addition, a survey was conducted of university staff and faculty to determine their attitudes towards the DEE model, which resulted in positive results.